BENCHMARKING PERFORMANCE MEASUREMENT SYSTEMS IN BOTSWANA’S CONSTRUCTION SECTOR - Mogale SABONE; Richard ADDO-TENKORANG (Journal of Construction Project Management and Innovation)
The performance of Botswana’s construction industry has been steadily declining in recent years. Furthermore, the industry has been docked with many projects that are not delivered on time, go over budget, sub-standard quality or are just abandoned. The frequency of occurrence of such projects has been alarming and has raised the question of whether there is a comprehensive system in place to monitor and control these projects. Some of the adverse effects of these delays and misappropriations are; costs escalating above budgeted values and quality of the deliverables shifting from the standard and agreed specification. Performance Measurement Systems (PMS) can be used to determine progress towards achieving certain goals and milestones in the life cycle of a project. These PMS are not new to the construction industry as they have been adopted in the industry for some time now. Therefore, the advantages of employing or implementing such systems are well documented but a lot of troubles apparently solvable by PMS are still encountered within Botswana’s construction industry.  A research survey was conducted on construction companies in Botswana with the purpose of finding out the extent of adoption of performance/progress measurement systems in Botswana’s construction industry and the barriers to their implementation in the industry. From the research it was found that most companies have not adopted PMS due to lack of understanding on the methods.